Into the field : human scientists of transwar Japan - Kadia, Miriam Kingsberg, 1981- (Stanford University Press, 2020)
Into the Field is a collective biography of the generation of Japanese human scientists who created ""objective"" field knowledge of human diversity to support imperial expansionism and control before 1945, and modernization under U.S. auspices thereafter.